2013
DOI: 10.3171/2013.7.peds1388
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of refractory status epilepticus in children

Abstract: Object Refractory status epilepticus (RSE) is a life-threatening neurological emergency associated with high morbidity and mortality. Affected patients often require prolonged intensive care and can suffer multiple complications. Surgical intervention to control RSE is rarely used but can obviate the risks of prolonged seizures and intensive care treatment. Authors of the present study analyzed their experience with the surgical management of patients suffering from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 35 publications
0
18
0
1
Order By: Relevance
“…Final outcome was seizure freedom (Engel Class I) in 7 patients, 90% seizure reduction (Engel Class II) in 4 patients, and persistent seizures in 4 patients (Engel Class III or IV). The authors concluded that SPECT is especially useful as it guided the invasive monitoring and surgical resections in 10/12 patients [26].…”
Section: Discussionmentioning
confidence: 99%
“…Final outcome was seizure freedom (Engel Class I) in 7 patients, 90% seizure reduction (Engel Class II) in 4 patients, and persistent seizures in 4 patients (Engel Class III or IV). The authors concluded that SPECT is especially useful as it guided the invasive monitoring and surgical resections in 10/12 patients [26].…”
Section: Discussionmentioning
confidence: 99%
“…One case series of 15 children with RSE who underwent surgical procedures reported that all had seizure control ranging from seizure freedom to substantial reductions, allowing transition out of the ICU. 128 Vagus nerve stimulation has been reported effective in several case reports, but efficacy generally occurs over a prolonged period.…”
Section: Refractory Status Epilepticusmentioning
confidence: 99%
“…A case series of 15 children with RSE who underwent surgical procedures reported that all had seizure control ranging from seizure freedom to substantial reductions, allowing transition out of the ICU. [70][Class IV]…”
Section: Other Therapiesmentioning
confidence: 99%